MAGMATISM OF THE HADEAN GEON IN EARTH DIFFERENTIATION - Balashov Yu.A. (My University, 2006)
Essential problems of the oldest geological stage in the Earth’s history (Hadean Geon) marked by formation of geospheres and their transformation during initial interaction remain highly debatable still today because of insufficient knowledge of the chemical characteristics and chronology of the early crust and mantle. The age estimates available for this stage (~4.0–4.4 Ga) were obtained only for the Archean crust based on detrital and captured (xenogenic) zircons. Today, such zircons have been found in the metasedimentary rocks and granitoids of three terranes in Western Australia and in Acasta granitoids of western Canada.
Keywords: Hadean Geon